Role of Ultrasonography in Diagnosis of Palpable Breast Lumps: One Year Cross Sectional Study - M.S. Sangolli, A.S. Gogate, U.D. Manoranjan* (Recent Research in Science and Technology, 2010)
Abstract Background: The breast is commonest site for development of cancer in female and accounts for around 1/5 of all malignancies in the sex. In the past few years ultrasonography of the breast for evaluation of radiologically dense breasts or cysts has been become the 1st line of investigation. Aims and Objectives: To assess the role of ultrasonography in diagnosis of palpable breast lumps. The most important clinical use of ultrasound imaging is its ability to differentiate between solid and cystic masses, benign and also by knowing the prior diagnosis the need for open biopsy and followed by surgery, the cost and time involved can be saved. In patients with dense breasts the FNAC may not hit the exact site of mass and can give inconclusive diagnosis. When Ultrasonography can pick up abscess of breast, needle aspiration can be done instead of incision and drainage. Breast ultrasonography should be considered as an extension of physical examination and it will improve the care available to patients and subsequently improve outcomes. Ultrasonography can expedite both diagnosis and treatment Results: On analysis, 68 patients were included in study.Â  The sensitivity of ultrasonography for malignancy was 89.47%. The specificity of ultrasonography was malignant & benign lesions 100%. The positive predictive value of ultrasonography was 100%. Conclusion: Ultrasound has higher sensitivity in diagnosing malignant lesions hence should be considered as first line diagnostic tool for breast lesions. Keywords: Ultrasonography, Breast lump